Clinical characteristics and outcomes of the first 63 adult patients hospitalized with COVID-19: An experience from Oman. Issue 7 (July 2020) - Khamis, Faryal; Al-Zakwani, Ibrahim; Al Naamani, Hamed; Al Lawati, Sultan; Pandak, Nenad; Omar, Muna Ba; Al Bahrani, Maher; Bulushi, Zakaryia AL; Al Khalili, Huda; Al Salmi, Issa; Al Ismaili, Ruwaida; Al Awaidy, Salah T.
Abstract: Introduction: To identify the clinical characteristics and outcomes of hospitalized patients with COVID-19 in Oman. Methods: A case series of hospitalized COVID-19 laboratory-confirmed patients between February 24th through April 24th, 2020, from two hospitals in Oman. Analyses were performed using univariate statistics. Results: The cohort included 63 patients with an overall mean age of 48 ± 16 years and 84% ( n = 53) were males. A total of 38% ( n = 24) of the hospitalized patients were admitted to intensive care unit (ICU). Fifty one percent ( n = 32) of patients had at least one co-morbidity with diabetes mellitus (DM) (32%; n = 20) and hypertension (32%; n = 20) as the most common co-morbidities followed by chronic heart and renal diseases (12.8%; n = 8). The most common presenting symptoms at onset of illness were fever (84%; n = 53), cough (75%; n = 47) and shortness of breaths (59%; n = 37). All except two patients (97%; n = 61) were treated with either chloroquine or hydroxychloroquine, while the three most prescribed antibiotics were ceftriaxone (79%; n = 50), azithromycin (71%; n = 45), and the piperacillin/tazobactam combination (49%; n = 31). A total of 59% ( n = 37), 49% ( n = 31) and 24% ( n = 15) of the patients were on lopinavir/ritonavir, interferons, or steroids, respectively. Mortality was documented in (8%; n = 5) of the patients while 68% ( n = 43) of the study cohort recovered. Mortality was associated with those that were admitted to ICU (19% vs 0; p = 0.009), mechanically ventilated (31% vs 0; p = 0.001), had DM (20% vs 2.3%; p = 0.032), older (62 vs 47 years; p = 0.045), had high total bilirubin (43% vs 2.3%; p = 0.007) and those with high C-reactive protein (186 vs 90 mg/dL; p = 0.009) and low corrected calcium (15% vs 0%; p = 0.047). Conclusions: ICU admission, those on mechanical ventilation, the elderly, those with high total bilirubin and low corrected calcium were associated with high mortality in hospitalized COVID-19 patients.